Native plants for the remediation of abandoned sulphide mines in Cyprus: A preliminary assessment. (15th November 2020) - Stylianou, Marinos; Gavriel, Ifigenia; Vogiatzakis, Ioannis N.; Zorpas, Antonis; Agapiou, Agapios
Abstract: Mining in Cyprus resulted in a significant number of abandoned sulphide mines without any rehabilitation measures. The present study aims to describe and compare the environmental parameters in three such mines with respect to water chemistry, waste dumps geochemistry, slope-topography and plant growth. The mines under study are that of Kokkinopezoula, North and South Mathiatis located at the northeast of the Troodos massif. A synopsis of the previous studies conducted for the above-mentioned mines is presented, which includes water and soil samples analyses. Although, in these areas environmental degradation is reported, there are some plants which grow naturally. Therefore, a preliminary attempt to report these plants is conducted, while remediation options presented in the literature including technosols, revegetation, phytoremediation and phytostabilization are proposed. Potential use of native plants such as Phragmites australis, Tamarix smyrnensis, Poaceae, Pinus brutia and Schoenus nigricans Poaceace could be applied for phytoremediation of the sulphide mines in Cyprus. These plants seem to have great strength at low pH values and high metal content in contaminated soils and water. The three mines under study are also compared with three other old mines located in the broader area of Cyprus; that of Xeros, Limni and Skouriotissa, which operated under similar climatic conditions. By improving abandoned mines environment with technosols, the action of native plants will be enhanced and thus work towards a successful phytoremediation treatment, resulting in the minimization of future pollutants generated by the solid waste dumps. Graphical abstract: Image 1 Highlights: Potential use of native plants such as Phragmites australis, Tamarix smyrnensis, Pinus brutia, Cistus creticus and Schoenus nigricans could be applied for phytoremediation of the sulphide mines in Cyprus. Native plants seem to have great strength at low pH values and high metal content in contaminated soils and water. By improving their environment with a technosol, native plants will be enhanced and work towards a successful phytoremediation treatment.